Navigating the New Arctic: Insights into Ship Activities, Ice Modeling, and Stakeholder Engagement in US Arctic Waters - Gedikli, Ersegun Deniz; Francis, Oceana; Hendrikse, Hayo; DEMİR, Özgür; Behnen, Jonas; Groeschel, Virginia; Peel, Grant (2024)
In this paper, we focus on investigating ship activities in the United States’ Arctic waters and developing new viscoelastic materials that can mimic specific ice behavior. This is a significant challenge, and we discuss potential positive outcomes and how the acquired knowledge can contribute to understanding ice behavior in Arctic and Sub-Arctic regions. We first define ice and ship statistics, providing a foundational understanding of potential ice–ship interactions. We then describe the development of thought experiments for wave–ice interactions and the creation of a numerical environment for modeling purposes. This step is crucial for simulating various scenarios related to ice and wave dynamics, ultimately contributing to the design of ships capable of navigating safely in diverse Arctic conditions. Finally, stakeholder and community engagement is addressed, recognizing the importance of involving local perspectives and insights to ensure practical, socially responsible, and effective solutions.